2013
DOI: 10.1007/s00384-013-1721-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Lgr5 correlates with resistance to 5-FU-based chemotherapy in colorectal cancer

Abstract: These results suggest that elevated Lgr5 level is associated with CRC progression and treatment response and has the potential to serve as a therapeutic target in CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 38 publications
7
66
2
Order By: Relevance
“…Regarding CRC, many study groups reported that LGR5 is overexpressed in CRC tissues and is associated with unfavorable outcome in CRC patients (24)(25)(26)(27). In the present study, although univariate analysis showed overexpression of LGR5 to be a possible biomarker of unfavorable outcome of CRC, its clinical usefulness in predicting relapse of CRC was not as expected.…”
Section: Discussioncontrasting
confidence: 50%
“…Regarding CRC, many study groups reported that LGR5 is overexpressed in CRC tissues and is associated with unfavorable outcome in CRC patients (24)(25)(26)(27). In the present study, although univariate analysis showed overexpression of LGR5 to be a possible biomarker of unfavorable outcome of CRC, its clinical usefulness in predicting relapse of CRC was not as expected.…”
Section: Discussioncontrasting
confidence: 50%
“…LSD1 inactivation was also found to selectively impair the growth of lung, breast and ovarian carcinoma cells that express Sox2, a pluripotent stem cell marker ). LGR5, a functional stem cell marker of CRC, can regulate the proliferation and colony formation of CRC cells (Kemper et al 2012;Hsu et al 2013). We therefore used CBB1003 as a probe to study the associations between LSD1 and LGR5 in CRC carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…LGR5 was shown to increase drug resistance, and in colon primary tumors, LGR5-high expression correlated with chemoresistance and lower disease-free and overall survival (16,17,20,23,42,43). Thus, an LGR5-targeting ADC may not only effectively treat gastrointestinal tumors, but also function to eliminate CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies using mouse models with loss of the tumor suppressor APC (adenomatous polyposis coli) gene have established that LGR5-positive stem cells are the cells-of-origin that drive intestinal and gastric tumor development (6,15). LGR5-high cancer cells have been shown to exhibit the properties of tumor-initiating cells or cancer stem cells (CSC), which retain the capacity for self-renewal (2,(15)(16)(17)(18)(19)(20). CSCs can fuel tumor growth, confer resistance to standard chemotherapy and radiation, and are likely to contribute to recurrent disease (21).…”
Section: Introductionmentioning
confidence: 99%